Athletes do not know the morphology of their feet - Celso Sánchez Ramírez (Asociación Española de Ciencias del Deporte, 2022)
The foot corresponds to the body segment that allows the exchange of forces between the support surface and the athlete's body; its morphology and function influence the quality of movement and body alignment. Moreover, the foot morphology can be modified according to the different adaptations that different sports cause, such as running, sport combat and team sports.  This work aimed to define the knowledge that a sample of athletes has about their Medial Longitudinal Foot Arch (MLFA), which has been classified as Cavus, Normal and Flat. A sample of 119 athletes, separated into three groups (runners, combat athletes, and team players), were given a self-perception questionnaire of their MLFA. Their responses were contrasted with the Arch Index (AI), which is a reliable objective measurement of the MLFA. Just 18.5% of the sample were able to identify their MLFA, as 67.2% stated they did not know, and 14.3% erred in their self-diagnosis. Combat athletes had the highest percentage who correctly identified their MLFA (25%). Association was found between the knowledge demonstrated by athletes and the sport they practiced (X2 = 9.926, df = 4, p = 0.04). The ignorance about MLFA by the athletes studied is presented as a problem of which consequences are unknown; this opens future research focused on the study of injuries caused by misalignment of the foot and the need to prescribe sports shoes as orthoses.